Antimicrobial Resistance in Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa Isolated from the Milk of Dairy Cows in Three Nigerian Cities (2012)
This study determined the safety of milk from dairy herds obtained by hand milking method from two major cattle producing States of Nigeria by investigating the presence of Escherichia coli 0157:H7 and their antibiotic susceptibility pattern. Forty seven milk samples from Kwara and 63 from Kaduna States were obtained from selected indigenous breeds of dairy cow. Bacteriological analysis by culturing on MacConkey agar (MAC) and subcultured on Sorbitol MacConkey agar (SMAC) were done. Escherichia coli 0157.H7 were confirmed serologically using latex agglutination kits (OxoidR UK). The isolates were tested for susceptibility to five commonly used antimicrobial agents and plasmid transfer was also carried out using E. coli K12 356 recipient. Out of the 61 non-Sorbitol fermenting (NSF) E. coli isolated from the samples 33(30.0%) were confirmed as E .coli 0157.H7 serotype. Antibiotic Susceptibility profile showed that all the isolates were resistant to one or multiple antibiotics, resulting in six different resistance patterns. Sulphadimidine resistance was the highest with all the isolates (100%) exhibited resistance to this drug while streptomycin had the highest sensitivity. Out of the seventeen E.coli 0157.H7 isolates tested for plasmid transfer, eleven (64.7%) transferred their resistance to the sensitive E. coli K12 356 enblock, while the remaining six showed segregation. The preponderance of E. coli O157 in this study indicated that greater proportion of milk being produced for human consumption in Nigeria were not wholesome and could posed threat of transmission of zoonotic pathogens. The high proportion of multidrug resistance exhibited by the isolates and the plasmid transfer is of public health significance as they could confer resistance on both pathogenic and non-pathogenic bacterial population in the consumers. More so, the milk which were obtained traditional unhygienic hand milking are either consumed raw or improperly pasteurized. Hygienic milking, pasteurization and judicious use of antibiotics after properly diagnosis and sensitivity test against newer antibiotics are recommended.